On the possibility of determining the parameters of the ionosphere when removing a nanosatellite from orbit using an uninsulated conductive tether - T. A. Bystranova; Yu. M. Zabolotnov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
Currently, one of the ways to quickly remove spent nanosatellites from orbit is the use of non-insulated conductive tether, during the movement of which an electrodynamic braking force arises in the Earth's magnetic field, transferring the nanosatellite to the trajectory of descent into the atmosphere. In this paper, the possibility of determining the concentration of electrons in the Earth's ionosphere from the resulting current distribution in an uninsulated tether during the deceleration of a nanosatellite is analyzed. It is shown that the concentration of electrons directly affects the position of the zero potential point on the cable and, therefore, this fact can be used to solve the problem. An algorithm for determining the electron concentration by the position of the zero potential point was developed. Numerical simulation of the process of determining the electron concentration during the deceleration of a nanosatellite is carried out, taking into account the unavoidable measurement errors.